A review of the state of research, policies and strategies in addressing leakage from reducing emissions from deforestation and forest degradation (REDD+) - Atmadja, S.; Verchot, Louis V. (2011)
Leakage from policies to reduce emissions from deforestation and forest dgradation (REDD+) must be monitored, measured and mitigated to ensure their efectiveness. This paper reviews research on leakage at the large (international and national) and small (subnational and project) scales to summarize what we already know, and highlight areas where research is urgently needed. Most (11 of 15) studies published until 2005 estimated leakage of fossil-fuel-based emissions from large-scale interventions such as the United Nations Framework Convention on Climate Change Kyoto Protocol. Many studies on leakage from landuse-based emissions more relevant for REDD+ emerged afterwards (11 of 15), mostly focusing on smaller-scale interventions (8 of the 11 studies). There is a deficiency in qualitative studies showing how leakage develops from an intervention, and the factors influencing this process. In–depth empirical research is needed to understand activities and actors causing emissions (Emissions), the way those activities move spatially in response to policies (Displacement), the way policies affect carbon (C) emitting activities (Attribution) and the amount of resulting emissions produced (Quantification). The cart is thence before the horse: the knowledge necessary to form practical and accurate working definitions, typologies and characterizations of leakage is still absent. Despite this, there is a rush to measure, monitor and mitigate leakage. The concept of leakage has not matured enough, leading to vague definitions of leakage, its components, and scale. We suggest ways to improve the concept of leakage and argue for more empirical research and at various scales to add to our collective knowledge of missions, Displacement, Attribution and Quantification.